キョクイキ タイキ ブッシツ ジュンカン ケンキュウ ノ ケイフ - 山内, 恭; ヤマノウチ, タカシ; Yamanouchi, Takashi (情報・システム研究機構 国立極地研究所, 2010)
P(論文) 国立極地研究所のプロジェクト研究「極域大気-海洋-雪氷圏における物質循環の解明」の全体像を概観した.この研究は,現場観測としては,南極での研究プロジェクト,第Ⅴ期( 1996-2000年度)の「南極大気・物質循環観測」,第Ⅵ期( 2001-2005年度)の「南極域における地球規模大気変化観測」,第Ⅶ期( 2006-2009年度)重点プロジェクト「極域宙空-大気-海洋の相互作用からとらえる地球環境システムの研究」の一部,および各期を通しての「大気微量成分モニタリング」,そして北極域スバールバル・ニーオルスン基地を中心とした大気観測に基づくものであり,さらに大気循環の解析的研究についても含めた.全体を通して,極域の大気・物質循環研究がこの15年でいかに進められてきたかを眺め,その研究の進展の跡をたどった.極域の物質循環,特に大気中物質の変動を中心に,大気循環との関わり,大気輸送との関連に重点をおいた.個々の研究や論文は,一つの物質の変化を限られた側面から見たに過ぎないものも多いが,全体を組み合わせることで,極域の大気・物質循環像に迫ることができた. An overview is given of the project of the National Institute of Polar Research (NIPR) "Study of Material Cycle in the Polar Atmosphere, Ocean and Cryosphere". Most of the subjects in the study had been conducted under related observational projects in the Antarctic, "Atmospheric circulation and material cycle in the Antarctic" (FY1996-2000), "Global Atmospheric Change in the Antarctic" (FY2001-2005), priority research project "Study on the Global Environmental System with the Interactions between Space, Atmosphere and Ocean", monitoring study on "Atmospheric Minor Constituents", observations in the Arctic, and analysis studies. Reviewing these 15 years of study and related projects, we find that the study revealed progress in understanding the "polar atmospheric circulation and material cycle". Even though each study or paper showed only one part of the variation of single atmospheric constituent, as a whole, we gained good understanding of features of the "polar atmospheric circulation and material cycle". departmental bulletin paper